The influence of the new act on cosmetic products on the improvement of the safety of use - Anna Pilarska; Agnieszka Ewa Zimmermann (Polish Pharmaceutical Society, 2020)
Cosmetic products are one of three categories of products that are associated with purchasing in pharmacies. This is mainly due to the high level of confidence in products bought in pharmacies and personal conviction concerning their safety. In fact, the requirements for cosmetics safety are the same for products sold in pharmacies, as well as in any other places. Frequently patients buying cosmetics in pharmacies have no awareness of the fact, that this category of products is regulated differently from medicinal products. It is crucial for patients, who have doubts about the safety of the products, to be able to obtain the necessary information from the pharmacist especially on how and to whom the adverse reaction should be reported. This study analyses the new act on cosmetic products, which has been enacted on January 1, 2019. It contains provisions that are to be an effective enforcement instrument for entities placing cosmetic products on the market to ensure compliance with the relevant obligations set out in Regulation (EC) No 1223/2009 of the European Parliament and of the Council of 30th November 2009 on cosmetic products. Cosmetic products are one of three categories of products that are associated with purchasing in pharmacies. This is mainly due to the high level of confidence in products bought in pharmacies and personal conviction concerning their safety. In fact, the requirements for cosmetics safety are the same for products sold in pharmacies, as well as in any other places. Frequently patients buying cosmetics in pharmacies have no awareness of the fact, that this category of products is regulated differently from medicinal products. It is crucial for patients, who have doubts about the safety of the products, to be able to obtain the necessary information from the pharmacist especially on how and to whom the adverse reaction should be reported. This study analyses the new act on cosmetic products, which has been enacted on January 1, 2019. It contains provisions that are to be an effective enforcement instrument for entities placing cosmetic products on the market to ensure compliance with the relevant obligations set out in Regulation (EC) No 1223/2009 of the European Parliament and of the Council of 30th November 2009 on cosmetic products.